A taxonomic study of the genus cryptolepis (periplocoideae: apocynaceae) - Joubert, Lize (University of the Free State, 2013)
Cryptolepis R.Br. (Apocynaceae, Periplocoideae) was taxonomically revised. Detailed descriptions of macro and micro-morphology, palynology, geographic distribution and ecological characteristics were presented. An identification key to the species was compiled and the nomenclature of all species was revised while all available type material was studied and lectotypes and neotypes were designated where necessary. Molecular phylogenetic analyses, based on the gene regions ITS, trnD–T and trnT–F, of representative species of 28 periplocoid genera and 22 Cryptolepis species were presented and the monophyly of Cryptolepis was evaluated. Historically a total of 81 species names and four subspecies names were published for Cryptolepis. However, a large number of species names were later placed in synonymy or transferred to other genera, while several new combinations were published. This resulted in a total of 29 accepted Cryptolepis species at the commencement of this study. Three new species, C. ibayana, C. thulinii and C. villosa, resulted from this study and the latter two were described in this thesis. One species, C. producta, was synonymised with C. oblongifolia. Cryptolepis, therefore, comprises a total of 31 species at present. In terms of species diversity, distribution and potential pharmaceutical and economic value, Cryptolepis is one of the most significant genera in the Periplocoideae. Cryptolepis grows throughout sub-Saharan Africa, the southern parts of Yemen, the island archipelago of Socotra, and southern Asia ranging from India to southern China, Taiwan, the Philippines and Indonesia. Most of the species grow in tropical forests or savannah, but 13 species are also adapted to arid environments. The majority of Cryptolepis species are concentrated in four centres of diversity along the east coast of Africa and on Socotra. These hotspots are associated with both arid and forest refugia in areas which have been regarded as local centres of endemism for a number of other plant taxa. The phylogenetic analysis of Cryptolepis indicates that most of these hotspots were colonized repeatedly by different Cryptolepis groups. In addition to the influence of climate shifts, edaphic conditions and also fire had a significant influence on species diversity and distribution in Cryptolepis. Macro and micro-morphological investigations indicated that numerous characters, including growth form, leaf shape and size, leaf epidermal characters, venation, inflorescence structure, floral structure and seed coat surface characters, are of diagnostic value at species level in Cryptolepis. However, the species can only be accurately identified by using a combination of these characters. The molecular phylogenetic analyses revealed that Cryptolepis is paraphyletic and, in order to establish a monophyletic genus, it was proposed that the circumscription of the genus be broadened to include Parquetina as a synonym of Cryptolepis. Several vegetative and reproductive characters showed a high degree of homoplasy, suggesting a high degree of morphological plasticity. This plasticity was also found at species level in C. oblongifolia, which showed significant variation in vegetative and reproductive features. This, together with a high tolerance for disturbance, has resulted in C. oblongifolia becoming the most widely distributed of all Cryptolepis species.

Cryptolepis R.Br. (Apocynaceae, Periplocoideae) is taksonomies hersien. Volledige beskrywings van die makro- en mikromorfologie, palinologie, geografiese verspreiding en ekologiese eienskappe is aangebied. 'n Uitkenningsleutel tot die spesies is opgestel, die nomenklatuur van al die spesies is hersien, terwyl alle beskikbare tipemateriaal bestudeer is en lekto- en neotipes is, waar nodig, aangewys. Molekulêre filogenetiese ontledings, gebaseer op die geenstreke ITS, trnD–T en trnT–F, van verteenwoordigende spesies van 28 periplokoide genusse en 22 Cryptolepis spesies is in die ondersoek ingesluit, en die monofilie van Cryptolepis is beoordeel. Histories is 'n totaal van 81 spesies en vier subspesies name vir Cryptolepis gepubliseer. 'n Groot aantal van hierdie spesiesname is egter later in sinonomie geplaas of na ander genusse oorgeplaas, terwyl 'n aantal nuwe kombinasies gepubliseer is. Met die aanvang van die huidige studie was daar dus 'n totaal van 29 erkende spesies in Cryptolepis. 'n Verdere drie nuwe spesies, C. ibayana, C. thulinii en C. villosa, is die resultaat van hierdie studie, waarvan die laasgenoemde twee in hierdie proefskrif beskryf is. Een spesie, C. producta, is in sinonomie met C. oblongifolia geplaas. Gevolglik sluit Cryptolepis tans 'n totaal van 31 spesies in. In terme van spesieverskeidenheid, verspreiding en potensiële farmaseutiese en ekonomiese belangrikheid is Cryptolepis een van die belangrikste genusse in die Periplocoideae. Cryptolepis kom dwarsdeur Afrika suid van die Sahara voor, maar ook in die suidelike deel van Jemen, in die Socotra eilandargipel en in suidelike Asië vanaf Indië tot suidelike Sjina, Taiwan, die Filippyne en Indonesië. Die spesies groei hoofsaaklik in tropiese woude of in savanna, maar 13 spesies word in droë omgewings aangetref. Die meeste Cryptolepis spesies is in vier diversiteitsentrums langs die ooskus van Afrika en op Socotra gekonsentreer. Hierdie brandpunte word met beide droë- en woudtoevlugnisse geassosieer in gebiede wat beskou word as plaaslike sentrums van endemisme vir 'n aantal ander planttaksons. Die filogenetiese ontleding van Cryptolepis het getoon dat hierdie brandpunte ook herhaaldelik deur verskillende Cryptolepis spesiegroepe gekoloniseer is. Benewens die invloed van klimaatsverskuiwings, het edafiese toestande en ook vuur spesiesdiversiteit en verspreiding in Cryptolepis duidelik beïnvloed. Makro- en mikromorfologiese ondersoeke het aangetoon dat 'n verskeidenheid eienskappe insluitende groeivorm, blaarvorm, blaar epidermale eienskappe, tipe bearing, bou van bloeiwyses, blomstruktuur en eienskappe van die saadhuid diagnostiese waarde op spesievlak in Cryptolepis besit. Die spesies kan egter slegs noukeurig geïdentifiseer word deur 'n kombinering van eienskappe te gebruik. Die molekulêre filogenetiese ontledings het aangetoon dat Cryptolepis parafileties is en ten einde 'n monofiletiese genus daar te stel, is voorgestel dat die omskrywing van Cryptolepis uitgebrei word deur insluiting van Parquetina as 'n sinoniem. Sekere vegetatiewe en voortplantingskenmerke het 'n hoë mate van homoplasie getoon, en het op 'n hoë mate van morfologiese plastisiteit gedui. Dit is veral op spesievlak in Cryptolepis oblongifolia waargeneem. Hierdie plastisiteit, gekoppel met die hoë mate van verdraagsaamheid teenoor versteuring, het tot gevolg gehad dat Cryptolepis oblongifolia die wydste verspreiding in die genus het.
Thesis (Ph.D (Plant Sciences))--University of the Free State, 2013
Keywords: Apocynaceae; Biogeography; Cryptolepis; Micromorphology; Nomenclature; Palynology; Periplocoideae; Phylogeny; Systematics; Taxonomy; Asclepiadaceae